MASJID TUA ALMUJAHIDIN WATAMPONE (Sejarah Pendiriaan dan Fungsinya : kaintannya dengan pendidikan islam) - Ridhwan Ridhwan (EKSPOSE, 2017)
This article discusses the standing history and function of the Almujahidin Watampone Old Mosque in Bone Regency. The results of the study show that the Almujahidin Old Mosque was founded by Fakih Amrullah around 1632 AD. He is Kadhi pertma in the Kingdom of Bone. The construction of the Almujahidin Mosque was intended for the royal family of Bone, as well as a place for implementing and fostering Islamic education. Before the kingdom of Bone integrated with the Indonesian Unitary State, the Kadhi of the Kingdom of Bone made the Old Mosque of Almujahidin their place of activity. Its function as a place of education continues, although Bone is no longer the Kingdom.